Transformation in the digital era: optimising social media for news coverage - Elva Ronaning Roem; Winda Vanisya (Faculty of Communications Science, Dr. Soetomo University, 2024)
The development of communication technology also refers to the evolution of social media, which provides numerous benefits for its users. Journalists, in carrying out their work, have also undergone a transformation by optimising social media as an initial source of news. This research discusses the transformation of journalists in the digital era, focusing on optimising social media in covering news. The aim of this research is to analyse the use of social media by exploring the challenges and opportunities faced by journalists in utilising these platforms to obtain information, interact with audiences, and disseminate news swiftly and widely while adhering to the Journalistic Code of Ethics. This study is qualitative research employing a case study approach, with data collection methods involving in-depth interviews with journalists from various media outlets in Indonesia. The results of this research indicate, first, that the role of social media has evolved into a crucial element in modern journalistic practice. Social media, initially regarded as a social platform, has now become a primary source of information for journalists when commencing news coverage. The rapid dissemination of information via social media facilitates journalists' access to real-time data, the latest news, and public opinion. The Codes of Ethics serve as a guide to ensure that, despite information originating from social media, the verification process, objectivity, and balance of news remain paramount.